Improving company communication activity amidst the СOVID-19 restrictions - Volodymyr Kyslyy; Tetyana Bondar; Yevhen Kabluchko; Hlib Lieonov (Health Economics and Management Review)
This study aimed to consider the essence and significance of the company communication activities and identify modern communications tools amidst the COVID-19 quarantine restrictions. The study object is the Like Center LLC communication activity. In the study frameworks, the company organizational structure, the staff list, and the job responsibilities were analyzed. Besides, the SWOT analysis was conducted to disclose the company organization's activities features. The authors examined the company's competitive environment using the 4P concept, which allowed identifying the company's main advantages and searches for solutions to existing problems in the communication activities. The methodology basis involved graphic and structural analysis, logical generalization to substantiate the goals, target audience, and communication strategy of Like Center LLC. The findings allowed developing the suggestions for forming a communication program of Like Center LLC under quarantine the COVID-19 restrictions. The authors emphasized the necessity to implement innovative communication tools for LLC «Like Center» such as 1) creating a chatbot, 2) launching a YouTube channel, 3) introducing educational activities (conferences and training on business education). In the study, the authors determined the main functions of the chatbot. The example of training for regular corporate customers was demonstrated. The feature of this training was using a smartphone as an assistant for quick access to information, control and register customers, a tool for evaluating the company efficiency, and a device for creating activities. After training, the clients could realize the received knowledge and skills into practice. The study proposed the topics for online conferences, determined the target audience. In the study, the authors suggested the YouTube channel action plan to expand the target audience. The obtained results indicated the possible prospects and the company's efficiency through improving the company communication system.